Hvor konservative er polske norskstudenter i sin språkbruk? Hunkjønnsmarkering i norskinnlæreres tekstproduksjon - Horbowicz, Paulina (Folia Scandinavica Posnaniensia, 2016)
The paper examines the phenomenon of the feminine gender, which in Bokmål is optional. The choice between the masculine and feminine forms is nevertheless not without meaning. It has been proved that if some nouns appear in feminine form earlier in a text, it implies the use of feminine gender on other nouns (Dyvik, 2012). Hence, the appearance of feminine marking on different words is mutually related, and may be shown to be consistent or not. The paper analyses texts written by Polish students of Norwegian on three different levels of language command (A2, B2/C1 and C2+) and investigates their use of feminine marking. The results show that the feminine gender is most often used by beginner learners, which confirms the initial hypothesis. Contrary to expectations, the most advanced students show inconsistency in their choice of feminine marking at least as often as beginner learners. The general conclusion is that the majority of Norwegian learners are not fully aware of the implications which come with the use of the feminine gender.